Isozyme diversity of Garcinia gummigutta (L.) N. Robson in Western Ghat region, South India - P A Mathew, Utpala Parthasarathy, G R Asish, K Jayarajan, R Aravind, B Krishnamoorthy (Journal of Spices and Aromatic Crops, 2010)
Isozyme genetic markers are efficient tools to study genetic variations within and betweenpopulations of less known wild species as well as for studies on spatial distribution of geneticvariation. A study was conducted with four important isozyme markers namely, peroxidase,polyphenol oxidase, esterase and superoxide dismutase in Garcinia gummigutta populationcollected from Western Ghats in South India. The cluster analysis of the marker bands showedthat most of the population from similar geographic locations was the first one to groupthemselves, though a significant pattern was not noticed. The mean percentage of polymorphicloci was 52.5%. Total heterozygocity was 0.97 which is consistent with the average of tropicaltree species.